Implementasi Model Assure untuk Mengembangkan Desain Pembelajaran di SD Negeri Empang Bahagia 3 Kota Tangerang - Magdalena, Ina; Febriyani, Nur; Mufidah, Wirdatul (YASIN, 2023)
In the field of education, especially in teaching and learning activities, instructional design is seen as a basic component or aspect for building learning designs. The ASSURE model is a choice and applicable instructional design for all teachers that can be taken when they want to carry out learning activities. The purpose of this research is to find out how the teachers of SD Negeri Empang Bahagia implement the ASSURE model in learning. The research design of this research is descriptive qualitative research because the research data was obtained from a questionnaire. The results of this study are practical ASSURE models to be implemented in teaching and learning activities.